Book Review - Terr, Vivian (Columbia Journal of Environmental Law, 2020)
COST-BENEFIT ANALYSIS AND ENVIRONMENTAL REGULATIONS: POLI- TICS, ETHICS, AND METHODS. Edited by Daniel Swartzman, Richard A. Liroff and Kevin G. Croke. Washington, D.C.: The Conserva- tion Foundation, 1982. Pp. xv, 196. 11.50.